2018
DOI: 10.1002/fsn3.561
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of filamentous fungi in maize destined for human consumption in South Africa

Abstract: One‐hundred maize samples were analyzed for fungal contamination using conventional and molecular methods. The percentage incidence of different genera isolated revealed the predominance of Fusarium (82%), Penicillium (63%), and Aspergillus species (33%) compared to other genera. Fusarium occurred in 90% and 74% of small scale and commercial samples, respectively, while Penicillium occurred in small scale and commercial samples at an incidence rate of 64% and 62%, respectively. However, among the species, Fusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…As other studies reported, some of the most prevalent genera in corn were Aspergillus, Cladosporium, Fusarium, Penicillium, and Trichoderma (Bhattacharya and Raha, 2012;Niaz and Dawar, 2009;Ekwomadu et al, 2018). In line with our study, Askun (2006) found that Fusarium (82%), Penicillium (63%), and Aspergillus species (33%) were the most predominant fungi in corn compared to other genera.…”
Section: Impact Of Selective Infrared Heating On Fungal Communitysupporting
confidence: 90%
“…As other studies reported, some of the most prevalent genera in corn were Aspergillus, Cladosporium, Fusarium, Penicillium, and Trichoderma (Bhattacharya and Raha, 2012;Niaz and Dawar, 2009;Ekwomadu et al, 2018). In line with our study, Askun (2006) found that Fusarium (82%), Penicillium (63%), and Aspergillus species (33%) were the most predominant fungi in corn compared to other genera.…”
Section: Impact Of Selective Infrared Heating On Fungal Communitysupporting
confidence: 90%
“…Mycotoxins produced by Fusarium species are found on grains cultivated on every continent. The susceptibility of maize to Fusarium fungi and mycotoxins contamination is well documented [51][52][53]. All the maize samples analyzed in this study were contaminated with an average of 5 to 24 out of 42 Fusarium mycotoxins, including 0 to 3 masked forms at the same time.…”
Section: General Mycotoxin Occurrence Datamentioning
confidence: 96%
“…Maize crops are very susceptible to fungal attacks, both in the field and during storage (Mutiga et al, 2019). Depending on environmental conditions, a fungal infection might be mainly produced by species of Aspergillus (Sserumaga et al, 2020), Fusarium (Castañares et al, 2019) and Penicillium (Ekwomadu et al, 2018). Such fungi possess a unique biochemical pathway to assimilate a vast array of available substrates which may result in the production of toxic secondary metabolites, such as mycotoxins (Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%